Liver proliferating cell nuclear antigen, BAX/Bcl-2 ratio, collagen, and polysaccharide accumulation as diagnostic tools in experimental hepatocellular carcinoma : BAX/Bcl-2 ratio, polysaccharide, collagen, and PCNA in hepatocellular carcinoma diagnosis - Abdel-Hamid , Nabil Mohie; Hassan , Mohamed K; Ahmed, Amal AM; Abd Allah, Sara Gamal; Anber, Nahla H. (Journal of Contemporary Medical Sciences, 2022)
Objectives: This experimental study was conducted to look for a sensitive diagnostic panel for early detection of HCC. Methods: Combination of diethyl nitrosamine (DENA, 200 mg/kg, IP, once), two weeks later, CCl4(3ml/kg/week), subcutaneously, for 6 weeks) induced HCC in rats. Sixteen male Wistar rats were divided into 2 groups, control, and HCC. Results: DENA plus CCl4 elevated serum alpha-fetoprotein, liver enzyme activity and depressed superoxide dismutase, reduced glutathione (GSH), elevated malondialdehyde. Also, depressed caspase-3, elevated collagen, polysaccharide accumulation, proliferating cell nuclear antigen in liver tissues, and depressed BAX / Bcl-2 ratio. Conclusion: Decreased BAX/Bcl-2 ratio, elevated collagen deposition, polysaccharide accumulation, nuclear proliferation, and tissue oxidative stress help in the early diagnosis of liver cancer.